Sexual functioning in patients with major depressive disorder in randomized placebo-controlled studies of extended release quetiapine fumarate. (25th September 2013) - Clayton, Anita H.; Locklear, Julie C.; Svedsäter, Henrik; McIntyre, Roger S.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective We evaluated sexual functioning from 6 acute, randomized, placebo-controlled studies (6–10 weeks) of once-daily extended release quetiapine fumarate (quetiapine XR) 50, 150, or 300 mg/day as monotherapy (Studies 1–4) or adjunct therapy (Studies 6–7) in major depressive disorder (MDD). Methods We present a pre-planned, non-inferiority analysis of quetiapine XR monotherapy versus placebo using Changes in Sexual Functioning Questionnaire (CSFQ) total score change (Studies 1–4). Post hoc analyses evaluated CSFQ total and domain scores for fixed-dose monotherapy (Studies 1–2), modified fixed-dose (Studies 3–4), and adjunct therapy studies (Studies 6–7). CSFQ data for active comparators (duloxetine [Study 2], escitalopram [Study 4]) are reported. Results Quetiapine XR monotherapy was non-inferior to placebo for sexual functioning (least squares mean [LSM] difference in CSFQ score change versus placebo, 0.16 [95% confidence interval: −0.59, 0.92]); LSM change in CSFQ score: 1.90, quetiapine XR (all doses) and 1.73, placebo. LSM differences versus placebo (95% confidence interval): 0.18 (−1.40, 1.75), duloxetine (Study 2); 0.16 (−1.77, 2.10), escitalopram (Study 4). LSM differences with adjunct quetiapine XR 150 mg/day (0.52; p = 0.338) or 300 mg/day (0.22; p = 0.679) were comparable with placebo plus antidepressants. Post hoc all-patient and gender-specific analyses were comparable for CSFQ total scores versus placebo with quetiapine XR 50, 150, or 300 mg/day, duloxetine, and escitalopram. Discussion Lack of negative effects on sexual functioning in patients with MDD may improve treatment acceptability. Conclusion Quetiapine XR (monotherapy or adjunct therapy) had an impact on sexual function that was comparable with placebo.